Immunization of preterm infants with GSK's hexavalent combined diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus-Haemophilus influenzae type b conjugate vaccine: A review of safety and immunogenicity. Issue 7 (8th February 2018) - Omeñaca, Felix; Vázquez, Liliana; Garcia-Corbeira, Pilar; Mesaros, Narcisa; Hanssens, Linda; Dolhain, Jan; Gómez, Ivonne Puente; Liese, Johannes; Knuf, Markus
Highlights: Data show no reason to delay DTPa-HBV-IPV/Hib vaccination in preterm/(V)LBW infants. The vaccine is immunogenic and well-tolerated in preterm/VLBW infants, although HepB/Hib response appeared lower. Benefit/risk resembles in healthy preterm/term infants and routine vaccines can be co-administered. 13–30% of medically stable preterm infants developed apnea after DTPa-HBV-IPV/Hib. Data for very preterm/VLBW infants are still limited, and more studies are necessary. Abstract: Background: Infants with history of prematurity (<37 weeks gestation) and low birth weight (LBW, <2500 g) are at high risk of infection due to functional immaturity of normal physical and immunological defense mechanisms. Despite current recommendations that infants with history of prematurity/LBW should receive routine immunization according to the same schedule and chronological age as full-term infants, immunization is often delayed. Methods: Here we summarize 10 clinical studies and 15 years of post-marketing safety surveillance of GSK's hexavalent vaccine (DTPa-HBV-IPV/Hib), a combined diphtheria-tetanus-acellular-pertussis-hepatitis-B-inactivated-poliovirus- Haemophilus influenzae- type-b (Hib) conjugate vaccine, when administered alone, or co-administered with pneumococcal conjugate, rotavirus, and meningococcal vaccines and respiratory syncytial virus IgG to infants with history of prematurity/LBW in clinical trials. Results: At least 92.5% of infants with history of prematurity/LBW as young as 24 weeks gestation in clinical studies were seropositive to all vaccine antigens after 3-dose primary vaccination with GSK's hexavalent DTPa-HBV-IPV/Hib vaccine, with robust immune responses to booster vaccination. Seropositivity rates and antibody concentrations to hepatitis B and Hib appeared lower in infants with history of prematurity/LBW than term infants. Between 13–30% of medically stable infants with history of prematurity developed apnea after vaccination with GSK's hexavalent DTPa-HBV-IPV/Hib vaccine; usually after dose 1. The occurrence of post-immunization cardiorespiratory events appears to be influenced by the severity of any underlying neonatal condition. Most cardiorespiratory events resolve spontaneously or require minimal intervention. GSK's hexavalent DTPa-HBV-IPV/Hib vaccine was well tolerated in co-administration regimens. Conclusion: GSK's hexavalent DTPa-HBV-IPV/Hib vaccine alone or co-administered with other pediatric vaccines has a clinically acceptable safety and immunogenicity profile when used in infants with history of prematurity/LBW for primary and booster vaccination. Additional studies are needed in very premature and very LBW infants. However, currently available data support using GSK's hexavalent DTPa-HBV-IPV/Hib vaccine to immunize infants with history of prematurity/LBW according to chronological age. Author Video: Author Video Watch what authors say about their articles